A novel cytoprotective function for the DNA repair protein Ku in regulating p53 mRNA translation and function. (10th March 2016) - Lamaa, Assala; Le Bras, Morgane; Skuli, Nicolas; Britton, Sébastien; Frit, Philippe; Calsou, Patrick; Prats, Hervé; Cammas, Anne; Millevoi, Stefania
Abstract: Ku heterodimer is a DNA binding protein with a prominent role in DNA repair. Here, we investigate whether and how Ku impacts the DNA damage response by acting as a post‐transcriptional regulator of gene expression. We show that Ku represses p53 protein synthesis and p53‐mediated apoptosis by binding to a bulged stem‐loop structure within the p53 5′ UTR. However, Ku‐mediated translational repression of the p53 mRNA is relieved after genotoxic stress. The underlying mechanism involves Ku acetylation which disrupts Ku–p53 mRNA interactions. These results suggest that Ku‐mediated repression of p53 mRNA translation constitutes a novel mechanism linking DNA repair and mRNA translation. Synopsis: Ku represses the translation of p53 under basal conditions. DNA damage‐induced acetylation of Ku abrogates Ku–p53 mRNA interactions, increasing the translation of p53 mRNA. Loss of Ku increases p53 protein expression levels. Ku interacts with a stem‐loop structure within the 5′ UTR of the p53 mRNA. Ku represses p53 mRNA translation and function in normal conditions. Acetylation of Ku after DNA damage abrogates Ku–p53 mRNA interactions. Abstract : Ku represses the translation of p53 under basal conditions. DNA damage‐induced acetylation of Ku abrogates Ku–p53 mRNA interactions, increasing the translation of p53 mRNA.